The Influence of the Use of Artificial Intelligence on the Effectiveness of Student Learning in Mataram City - Harianti, Indah Fajri; Nabila, Rizky; Wadihar, M. Nur Wazda; Ahmad, Lalu Daffa Al; Wea, Yohanes Emanuel Dala; Patty, Elyakim Nova Supriyedi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of digital technology has driven the widespread use of Artificial Intelligence (AI) in learning, but its use has not been accompanied by an adequate understanding of student perceptions of its contribution to the learning process. This study aims to analyze student perceptions of the use of Artificial Intelligence in learning in Mataram City. The study used a quantitative approach with a survey method. Data were collected through a Likert-scale questionnaire distributed to students who have utilized AI in academic activities. Data analysis was conducted descriptively using average values ​​and percentages. The results showed that the level of AI utilization was in the high category with an average value of 3.90, while student perceptions of learning were in the moderate category with an average value of 3.75. These findings indicate that students view AI as a technology that helps obtain information, understand lecture material, and complete academic assignments more efficiently. However, the use of AI still requires digital literacy and critical thinking skills so that its use supports the learning process optimally. The results of this study provide input for universities in designing learning policies and strategies that integrate AI responsibly